Dynamic damage constitutive model of cemented sand and gravel material. Issue 23 (11th August 2022) - Zhang, Xiancai; Li, Po; Huang, Hu
Abstract: Cemented sand and gravel (CSG) material is a typical elastic-plastic material, the failure mechanisms and the mechanical properties were greatly related to the loads and the mixing proportions. The stress-strain curves showed obvious nonlinear hysteresis loops under cyclic loadings, and the cumulative damage size affects the fatigue life of materials. Based on the test results, the non-linear damage evolution law of CSG materials under the cyclic loading was further studied. The results showed that the relationship curves between the damage variables and the cumulative strain were index under different loadings. A dynamic damage constitutive model was founded according to the test results which can reveal the damage process of CSG materials under different loading types and the upper limit stress ratios.